Assessment of Functional and Pasting Properties of Fresh Orange Maize Hybrids and Open-Pollinated Varieties as Influenced by Genotype, Harvesting Time, and Growing Location - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Menkir, Abebe; Adesokan, Michael; Olaofe, Olorunfemi (Frontiers in Nutrition, 2021)
The present study describes the effects of genotype and maturity level on the functional and pasting properties of fresh orange maize hybrids and open-pollinated varieties (OPVs). Eight fresh orange maize hybrid and OPV, including the control, were harvested at three stages: 20, 27, and 34 days after planting (DAP). The maize materials were freshly harvested, lyophilized, and characterized for their pasting and functional properties. Peak viscosity, final viscosity, and swelling power increased between 20 DAP and 27 DAP for the OPVs. Also, water absorption capacity increases between 20 and 27 DAP for the maize hybrids, with a decreasing trend between 27 and 34 DAP. Genotypes 2 from the orange maize hybrid and 5 amongst the OPV were outstanding with the highest peak viscosities, indicating good final product quality. Overall, the interaction of location and stages of maturity significantly affects the pasting and functional properties of the orange OPV and maize hybrids. In contrast, the effects of genotype and location were not significant on their functional and pasting properties. Maize breeders could use the information from this study to select the best maize genotypes suitable for consumers' preferred product quality and the appropriate harvesting period for the selected maize genotypes.